ANALISA TEGANGAN VON MISES PADA ALAT BANTU JALAN (WALKER) - Sadeli Jokowiyono; Santoso Mulyadi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2012)
Movement for a walk is a function that needs to be helped, especially for the elderly because they experienced degradation of function or sick, one of them is degradation of the body's energy balance. Not uncommon among those who have trouble for walking, that is because the degradation on muscle strength in the limbs, for example, arm muscles, hand muscles, limb muscles, and leg muscles. Moreover, if the condition is accompanied by degenerative diseases such as osteoporosis, Parkinson's, stroke, knee pain, and fractures. A walker, making the right solution. One of the tools is Walker. Walker is an assistant to a very lightweight, portable, high waist, is made of metal pipe, and this tool comes with two handles that serves as a place that used to hold users and is equipped with four sturdy legs as the pedestal. While the power of the framework are analyzed with the help of CATIA V5R14 software is to determine the stress that occurs in order to operate as a walker. It appears that the greatest stress occurs is still under tension permission of the material itself. Stress equivalent (Von-Mises stress) that occurs should not exceed 1.583333e+007 N/m2 while the voltage that occurs on the order of 1.77e +005 N/m2 walker located at the foot of the minimum voltage while working on the framework of the 6.98e-009 N/m2 located on the frame. Key words: walker, von mises stress and framework.